Knowledge Management Implementation In Muhammadiyah Elementary School Of Pendowoharjo - Fauzi, Hafidh Nur; Mufti, Umam (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2019)
Abstract— Knowledge Management is a systematic step in managing knowledge and various information from individuals and organizations to be able to compete in order to add value and innovation. In the other hand, knowledge is one of the agency's assets and can be a separate competitive advantage if it can be managed properly. Current problems are [1]technological developments and increased competition between educational institutions. If an educational institution does not have good knowledge management, of course, it will be left behind. Good management is needed and applied optimally. In Muhammadiyah Elementary School of Pendowoharjo, there are two management implementation aspects, namely identification of knowledge and identification of structures. Tacit and explicit factors as patterns of knowledge management development also require attention. If all of these factors are properly considered and applied, it will create a favorite school that has good knowledge management.